Gambaran Perilaku Patuh Protokol Kesehatan Mahasiswa Anggota Unit Kegiatan Mahasiswa (UKM) Universitas Jenderal Soedirman Pascavaksinasi Covid-19 - Nur Oktafiani; Annas Sumeru; Akhyarul Anam (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Background: The transmission of Covid-19 continues to this day, all strategic and policy efforts are carried out by the government to prevent the spread of Covid-19. One of the important strategies currently being carried out by the government is to carry out mass vaccination against Covid-19. A person who has been vaccinated against Covid-19 still has a risk of being able to infect and be infected with Covid- 19 if they do not apply health protocols properly. This research has been done a lot, but research on student members of UKM has never been done. Therefore, researchers are interested in conducting research on the description of the behavior of complying with the health protocols of students who are members of the Jenderal Soedirman University student activity unit after the Covid-19 vaccination. Method: This quantitative descriptive study used a cross-sectional design. A total sample of 314 UKM member students was taken using a simple random sampling method and data collection for this study used a questionnaire via a Google form. The results of the analysis are presented in the form of frequency distribution tables and percentages. Results: The behavior of obeying the health protocols of students who are members of the Jenderal Soedirman University student activity unit after the Covid-19 vaccination is included in the level of compliance with a sufficient percentage of 50.6%. The behavior of complying with the health protocol after the Covid-19 vaccination is based on the characteristics of respondents who have a good level of behavior, namely at the age of 21 years (33.1%), female (79.7%), from the 2020 class (34.5%), coming from FIKES (23%), members of UKM KSR PMI (14.2%), and has been vaccinated against Covid-19 dose 2 (97.3%). Conclusion: Most of the student members of the UKM members of Jenderal Soedirman University have sufficient behavior to comply with the post-Covid-19 health protocol.